Supplementation with vitamin D and insulin homeostasis in healthy overweight and obese adults: A randomized clinical trial. Issue 3 (May 2021) - Ebadi, Seyed Alireza; Sharifi, Laleh; Rashidi, Elaheh; Ebadi, Seyed Shayan; Khalili, Shayesteh; Sadeghi, Soheila; Afzali, Nikta; Shiri, Sakineh Moghadam
Abstract: Introduction: Hypovitaminosis D which is a frequent problem in overweight and obese individuals, seems to interfere with cells responsible for control of glycemic status. Therefore, the current research intended to study the impact of supplementation with vitamin D on insulin homeostasis among healthy obese and overweight individuals. Methods: The current study was conducted among obese or overweight individuals who had hypovitaminosis D. After separation of participants into two groups, one group received vitamin D pearls (50, 000 IU/weekly) for eight weeks, whereas another group received a placebo over the same period. Next, the level of vitamin D, fasting blood sugar (FBS), fasting insulin, Homeostasis Model Assessment 2 for Insulin Resistance (HOMA2-IR), Function of β-cell (HOMA2-β), and Insulin Sensitivity (HOMA2-S) and lipid profile of participants were evaluated. Results: Overall, 67.2% of the participants were female. No considerable difference was observed concerning biochemical parameters among the study groups at baseline. After eight weeks, the mean (SD) level of vitamin D was significantly lower in the placebo group than those in the vitamin D group. (38.6 ± 8.1 vs. 14.9 ± 6.4; P < 0.001). The patients who received vitamin D had significant lower levels of FBS (P < 0.001), fasting insulin (P < 0.001), HOMA2-IR (P < 0.001), and HOMA2-β (P = 0.03), than the placebo group. The HOMA2-S was significantly enhanced in vitamin D group, while it reduced in another group (P < 0.001). However, no considerable decrease was found in triglyceride, cholesterol, high-density lipoprotein or low-density lipoprotein. Conclusion: Supplementation with vitamin D improved sensitivity to insulin and pancreatic function of β cells of healthy overweight and obese adults.